Neo-Hapai : a typographic representation of Shanghai : a thesis presented in partial fulfilment of the requirements for the Master of Design at the College of Creative Arts, Massey University, Wellington, New Zealand - Qian, Xiang (Massey University, 2012)
Many people who are interested in the art of typography want to challenge the conventional understanding of type and express it in a distinctive way. This project examines the aesthetics behind the use of typefaces and typographic composition. The focus of this study is on investigating how the essence of a physical location can be communicated through the medium of typography and other figurative language. It explores this through a typographic representation of the Chinese city of Shanghai. It will draw upon Shanghai’s history and cultural values, and transform it into a distinctive letterform, then compound it with patterns and colours to illustrate the city through typographic expression. This project will be realised entirely with type, colour, texture, shape and abstract images.
Keywords: Graphic design; Typography; Shanghai